(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Unintended pregnancy is well recognized reproductive health problem in developing countries like Bangladesh. It is more problematic in rural Bangladesh where illiteracy, poverty and empowerment crisis of women are common scenarios. Methods: This cross-sectional study was conducted at Shahdaulatpur village in Mainamati union of Comilla District during the period from July 2017 to June 2018. The study enrolled 317 rural women selected by systematic random sampling technique. Mixed method approach was introduced for data collection to find out the determinants and outcomes of unintended pregnancy among rural women. Focus group discussions and in-depth interviews were arranged for qualitative data and quantitative data were collected through face to face interview by pretested questionnaire. Ethical issues were considered in all aspect of the study. Results: Mean age of the rural women was 22.1 years with standard deviation of (SD) ± 3.6 years. The average monthly income of the family was 10732 ± 3228 Taka. Among the respondent more than half (55.2%) used contraceptive methods. Oral contraceptive pill (OCP) was their first choice (40.9%) and injections (19.8%) were common among the users of invasive family planning methods. Male participation in contraceptive use was only 8.8%. More than one-third (35.6%) had history of unintended pregnancy and among them majority (70.8%) had mistimed pregnancy and rest of them (29.2%) had unwanted pregnancy. The outcomes of the unintended pregnancy were mostly unplanned birth (93.4%) with (2.6%) miscarriages and termination of pregnancy by (4.4%) menstrual regulation (MR) or abortion. Age and educational status and monthly family income of rural women showed very high significant association with unintended pregnancy (p<0.001). Conclusion: As the quality of future human resource depends on healthy mother and safe motherhood, improvement of family planning knowledge should be given top priority. Hence, care should be taken to improve the status of knowledge and awareness about family planning. JOPSOM 2023; 42(2): 29-35